Mobile Learning and Artificial Intelligence to improve teaching-learning process in ICT global market age - Todino, Michele Domenico; Desimone, Giuseppe; Kidiamboko, Simon (Studi sulla Formazione/Open Journal of Education, 2022)
Opportunities offered through mobile devices in education are debated in the pedagogical scientific community in last years, since they were realized that contemporary society has undergone significant changes, in conjunction with a noteworthy spread of technological tools. More in details, PCs, tablets, smartphones, have become part of every individual’s life in a pervasive way, becoming indispensable and, in some ways, they are conditioning each life, thus they are conditioning education and the teaching-learning process. Among various opportunities offered by Media Education. More in details, in this work it is a broad range exploration of some relations that M-Learning and Artificial Intelligence have with ITC global market and Sub-Saharan higher education.